2016
DOI: 10.1016/j.scitotenv.2016.04.209
|View full text |Cite
|
Sign up to set email alerts
|

Land use effects on pesticides in sediments of prairie pothole wetlands in North and South Dakota

Abstract: Prairie potholes are the dominant wetland type in the intensively cultivated northern Great Plains of North America, and thus have the potential to receive pesticide runoff and drift. We examined the presence of pesticides in sediments of 151 wetlands split among the three dominant land use types, Conservation Reserve Program (CRP), cropland, and native prairie, in North and South Dakota in 2011. Herbicides (glyphosate and atrazine) and fungicides were detected regularly, with no insecticide detections. Glypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…For the seven most frequently detected herbicides (Table 3), only glyphosate and AMPA, and clopyralid, were more prevalent in wetlands on minimum‐tillage farms than in wetlands on organic farms. Similarly, McMurry et al (2016) observed that glyphosate was more prevalent in sediments of wetlands in croplands than in sediments of wetlands in native pasture where it was not used. Both glyphosate and clopyralid have high relative use in the study area with glyphosate having the highest use of all herbicides (Table 2).…”
Section: Discussionmentioning
confidence: 90%
“…For the seven most frequently detected herbicides (Table 3), only glyphosate and AMPA, and clopyralid, were more prevalent in wetlands on minimum‐tillage farms than in wetlands on organic farms. Similarly, McMurry et al (2016) observed that glyphosate was more prevalent in sediments of wetlands in croplands than in sediments of wetlands in native pasture where it was not used. Both glyphosate and clopyralid have high relative use in the study area with glyphosate having the highest use of all herbicides (Table 2).…”
Section: Discussionmentioning
confidence: 90%
“…Elevated soil nitrate concentrations and N 2 O emissions have been identified in cropland associated with wetlands, ostensibly due to inputs of N-based fertilizers (Bedard-Haughn et al 2006;Tangen et al 2015). Moreover, various agrichemicals (e.g., herbicides and fungicides) have been identified in sediments and tissues of wetland biota (e.g., Belden et al 2012;McMurry et al 2016;Venne et al 2008). McMurry and others (2016) found that glyphosate concentrations in soils were more than four times greater in cropland wetlands than grassland wetlands.…”
Section: Sediment Nutrient and Chemical Runoffmentioning
confidence: 99%
“…Abraxis Life Technologies™ provides field and labbased ELISA testing kits for several pesticides tested in various matrices listed in the National Environmental Methods Index. Numerous articles have proven the suitability of Abraxis pesticide kits, especially for the analysis of glyphosate [13][14][15]. For OP and CPs, a colorimetric assay ELISA screen kit (Microtiter Plate: 96 Test) was purchased from Abraxis Inc.…”
Section: Introductionmentioning
confidence: 99%